Managing Cloud Security Using Energetic Information Flow Control - Babu Renga Rajan, S.; Pushpa Ranjini, D.; Shanmuga Sundari, B.; Haseena Beevi, A.; Meenakshiammal, R. (Asian Journal of Engineering and Applied Technology, 2015)
Most of the cloud computing solutions used today does not ensure security. Although methods like access control list, firewall and cryptography impose limits on information that is released by the system, they provide no guarantee about information propagation. We propose a Decentralized Information Flow Control (DIFC) that is integrated into the PaaS cloud model. This enhances security by associating labels with the data it protects. This datacentric security mechanism tracks and limits data propagation.